PIROLISIS LIMBAH KULIT NANGKA MENJADI ARANG AKTIF DAN ASAP CAIR DENGAN AKTIVATOR LARUTAN NATRIUM KHLORIDA - Ani Purwanti; Achmad Thesa Widhaswara; Endri Santoso (PROSIDING SNAST, 2018)
Jackfruit (Artocarpu sheterophyllus) is a fruit plant that belongs to a group of tropical plants. During this time, jackfruit harvested for its ripe fruit meat, often used fresh or processed into various types of food. In general, jackfruit skin is only thrown away and underutilized. As jackfruit skin biomass has high organic composition and charcoal content, it has the potential as raw material for making activated charcoal and liquid smoke with pyrolysis process. Activated charcoal production was carried out by pyrolysis process, which is charcoal without contact with air. Jackfruit skin waste that had been cut with a size of 1 cm2 was dried first. After drying process, jackfruit skin waste was analyzed for water content and ash content then the pyrolysis process can be done. The pyrolysis process was carried out using temperature and time variations. The charcoal produced was soaked in the activator of NaCl solution with variations in concentration and soaking time. Based on the research that has been done with 150 grams of raw material, the best results were obtained at the process of pyrolysis temperature of 570ºC and pyrolysis time of 60 minutes, with a concentration of 20% NaCl solution and 34 hours of soaking time. From this process, 53 mL of liquid smoke was produced and the charcoal activity obtained was 331.105 mg/g. This charcoal activity is still below the standard, which is 750 mg/g (SNI 06-3730-1995).